The Dynamics of Citizenship Education in the Context of Political Reform - El Hadi, Amer; Kamel, Said (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Algeria's political transitions, marked by constitutional amendments in 2016 and 2020, have sparked efforts to integrate democratic principles and civic values into educational frameworks. This study examines the dynamics of citizenship education in the context of Algeria's political reforms. The research explores citizenship education's role in fostering civic participation and aligning educational content with national democratic aspirations. The methodology employs a mixed-methods approach, conducted throughout 2023, involving 500 respondents, including educators, policymakers, and students from diverse locations such as Algiers, Oran, Constantine, Tlemcen, and Setif. Quantitative surveys assess perceptions and effectiveness, while qualitative interviews and focus groups provide deeper insights into stakeholders' experiences and expectations. Findings reveal that citizenship education in Algeria demonstrates significant potential in promoting civic engagement and aligning with democratic ideals. However, challenges persist, such as balancing traditional cultural values with modern democratic principles, ensuring adequate teacher training, and addressing political constraints that hinder open dialogue. The discussion highlights the need for a comprehensive curriculum, participatory teaching methods, and a political environment conducive to civic learning. Future research could explore sector-specific impacts of citizenship education and the long-term outcomes of integrating democratic principles into curricula. These insights could guide policymakers and educators in designing more effective educational reforms tailored to Algeria's unique socio-political context.